Slip Sliding Away: Further Union Decline in Germany and Britain - Addison, John T. (2010)
This paper presents the first comparative analysis of the decline in collective bargaining in two European countries where that decline has been most pronounced. Using workplace-level data and a common model, we present decompositions of changes in collective bargaining and worker representation in the private sector in Germany and Britain over the period 1998-2004. In both countries within-effects dominate compositional changes as the source of the recent decline in unionism. Overall, the decline in collective bargaining is more pronounced in Britain than in Germany, thus continuing a trend apparent since the 1980s. Although workplace characteristics differ markedly across the two countries, assuming counterfactual values of these characteristics makes little difference to unionization levels. Expressed differently, the German dummy looms large.